Energy flux partitioning and evapotranspiration in a sub‐alpine spruce forest ecosystem - Gaofeng, Zhu; Ling, Lu; Yonghong, Su; Xufeng, Wang; Xia, Cui; Jinzhu, Ma; Jianhua, He; Kun, Zhang; Changbin, Li (Hydrological processes, 2014)
In this study, we examined the year 2011 characteristics of energy flux partitioning and evapotranspiration of a sub‐alpine spruce forest underlain by permafrost on the Qinghai–Tibet Plateau (QPT). Energy balance closure on a half‐hourly basis was H + λE = 0.81 × (Rₙ − G − S) + 3.48 (W m⁻²) (r² = 0.83, n = 14938), where H, λE, Rₙ, G and S are the sensible heat, latent heat, net radiation, soil heat and air‐column heat storage fluxes, respectively. Maximum H was higher than maximum λE, and H dominated the energy budget at midday during the whole year, even in summer time. However, the rainfall events significantly affected energy flux partitioning and evapotranspiration. The mean value of evaporative fraction (Λ = λE/(λE + H)) during the growth period on zero precipitation days and non‐zero precipitation days was 0.40 and 0.61, respectively. The mean daily evapotranspiration of this sub‐alpine forest during summer time was 2.56 mm day⁻¹. The annual evapotranspiration and sublimation was 417 ± 8 mm year⁻¹, which was very similar to the annual precipitation of 428 mm. Sublimation accounted for 7.1% (30 ± 2 mm year⁻¹) of annual evapotranspiration and sublimation, indicating that the sublimation is not negligible in the annual water balance in sub‐alpine forests on the QPT. The low values of the Priestley–Taylor coefficient (α) and the very low value of the decoupling coefficient (Ω) during most of the growing season suggested low soil water content and conservative water loss in this sub‐alpine forest. Copyright © 2013 John Wiley & Sons, Ltd.